Johann Peter Kirschs "römischer" Zugang zur Wissenschaft am Beispiel der Epigraphik - Schaaf, Ingo 1979- (2025)
"Johann Peter Kirsch's "Roman" approach to science using the example of epigraphy" - The present article explores an aspect of Johann Peter Kirsch's scholarly activity that has received relatively little attention to date - namely, his work in the field of inscriptions and, in connection with this, the question of the extent to which this engagement can be seen as "Roman" in character. This exemplary examination proceeds in three thematic steps, with a focus on Kirsch's activities during his early years in Switzerland: First, by tracing the role of the Christian archaeologist and epigraphist Giovanni Battista de Rossi in Kirsch's appointment to the Fribourg chair, and examining how de Rossi's material legacy came to benefit the newly founded seminar there. Then, by attempting to shed light on Kirsch's study on acclamations and prayers of early Christian funerary inscriptions and the context in which it was written. Finally, in a third step, Kirsch's rectorial address of 1898 - dedicated to Christian epigraphy and its importance for Church history research - will be examined more closely, particularly for statements by Kirsch that may be interpreted as programmatic.